Notes on the distribution of Brasenia schreberi (Cabombaceae) in the Neotropics, with a new country record for Costa Rica - Acuña Castillo, Rafael (2021)
La investigación contó con el patrocinio de la Sra. Myrna Stewart y la Sra. Amanda Bennett.